Global Proteomics Analysis of Protein Lysine Methylation. (1st November 2016) - Cao, Xing‐Jun; Garcia, Benjamin A.
Abstract: Lysine methylation is a common protein post‐translational modification dynamically mediated by protein lysine methyltransferases (PKMTs) and protein lysine demethylases (PKDMs). Beyond histone proteins, lysine methylation on non‐histone proteins plays a substantial role in a variety of functions in cells and is closely associated with diseases such as cancer. A large body of evidence indicates that the dysregulation of some PKMTs leads to tumorigenesis via their non‐histone substrates. However, most studies on other PKMTs have made slow progress owing to the lack of approaches for extensive screening of lysine methylation sites. However, recently, there has been a series of publications to perform large‐scale analysis of protein lysine methylation. In this unit, we introduce a protocol for the global analysis of protein lysine methylation in cells by means of immunoaffinity enrichment and mass spectrometry. © 2016 by John Wiley & Sons, Inc.